6m-3=-5/7m+496/7

Simple and best practice solution for 6m-3=-5/7m+496/7 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 6m-3=-5/7m+496/7 equation:


m in (-oo:+oo)

6*m-3 = (-5/7)*m+496/7 // - (-5/7)*m+496/7

6*m-((-5/7)*m)-(496/7)-3 = 0

6*m+(5/7)*m-496/7-3 = 0

47/7*m-517/7 = 0 // + 517/7

47/7*m = 517/7 // : 47/7

m = 517/7/47/7

m = 11

m = 11

See similar equations:

| 5/7t+5/6=-3t+815/42 | | -9-1/7a=-7a-67/7 | | 5+1/4d=-5d+325/44 | | 5d+9/10=-2/3d-313/30 | | n-8=-172/21+3/7n | | -1-1/2t=7t-47/2 | | 5x-4=-16+4x | | n-6=-69-6n | | 1/7-5b=2b-47/14 | | -1/2x+7=-4x+35/4 | | -2/7n+2=-16/7+4n | | 6+4/5t=-3/7t+878/175 | | 1/4+5/7a=5a-119/4 | | -6+1/5b=7b-100/11 | | -7w+2/3=-7/3-4w | | 5/6+5/6x=-6/7x+565/252 | | -3/7w-3/10=139/70-w | | 6/7w+1/4=-2w+67/28 | | 4b-10=-10-6b | | 4/9-6a=-2a-20/9 | | n-2/7=31/14+1/2n | | 1/5k+7/8=-9/8+3/5k | | -2/5-5/7x=-2/3x-61/165 | | b+9=11-b | | 2/3-3n=3/7n-70/3 | | 5m+7=7m+29 | | -8-3k=6k-14 | | 4+5/6b=-4b+169/6 | | -1/3a-1/5=-1/5+a | | -1/3d-5/6=239/30+2/5d | | -6/7+1/4x=6/7x+4 | | 2x-3x=-36+24 |

Equations solver categories